2005
DOI: 10.1021/jo051079z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofurans with Remote Bromide Functionality by Domino “Ring-Cleavage-Deprotection-Cyclization” Reactions of 2-Alkylidenetetrahydrofurans with Boron Tribromide

Abstract: [reaction: see text] Bromination and subsequent Suzuki reactions of 2-alkylidenetetrahydrofurans, readily available by [3+2] cyclizations, afforded 1'-(2''-methoxyphenyl)-2-alkylidenetetrahydrofurans. Treatment of the latter with boron tribromide and subsequent addition of water resulted in the chemoselective formation of functionalized benzofurans containing a remote bromide functionality. The products are formed by a new domino "ring-cleavage-deprotection-cyclization" reaction. The addition of an aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The following demethylation step is not very efficient due to the presence of the second methoxy group [25]. 4-(2-hydroxyphenylcarbonyl)-7-methoxy-1-phenylbenzopyran 5 was isolated after purification with 23% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The following demethylation step is not very efficient due to the presence of the second methoxy group [25]. 4-(2-hydroxyphenylcarbonyl)-7-methoxy-1-phenylbenzopyran 5 was isolated after purification with 23% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their important bioactivities and pharmaceutical applications, a number of synthetic methods have been developed for the synthesis of substituted naphtho [1,2-b]furans [24][25][26][27][28]. Recently, the synthesis of naphtho [1,2-b]furans using In(OTf) 3 and Fe-Pd bimetallic nanoparticlescatalyzed reactions was reported [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[2d-f] Considerable efforts have thus been directed towards the discovery of efficient methods for their synthesis. [3][4][5][6] Despite remarkable advances in benzofuran synthesis, most of the traditional methods suffer from harsh conditions, limited functional group tolerability, and/or the cost of the catalytic system. [3][4][5][6] Furthermore, the assembly of carbonylated benzofuran scaffolds remains a great challenge.…”
mentioning
confidence: 99%
“…Without TEMPO, the nitration/cyclization product (2-(nitromethyl)benzofuran-3-yl)(phenyl)methanone (4 a) was isolated in 23 % yield (entry 3). Three other solvents, namely MeCN, EtOAc, and toluene, effected the reaction but were inferior to DMF (entries [4][5][6]. Screening the effect of the reaction temperature revealed that higher temperatures were favorable, and 40 8C was found to be the preferred temperature (entries 1, 7, and 8).…”
mentioning
confidence: 99%